A Life-Long Approach to Physical Activity for Brain Health - Macpherson, Helen; Teo, Wei-P.; Schneider, Luke A.; Smith, Ashleigh E. (Frontiers in Aging Neuroscience, 2017)
It is well established that engaging in lifelong physical activity can help delay the onset of many chronic lifestyle related and non-communicable diseases such as cardiovascular disease, type two diabetes, cancer and chronic respiratory diseases. However, growing evidence also documents the importance of physical activity for brain health, with numerous studies indicating regular engagement in physical activities may be protective against cognitive decline and dementia in late life. Indeed, the link between physical activity and brain health may be different at each stage of life from childhood, mid-life and late life. Building on this emerging body of multidisciplinary research, this review aims to summarise the current body of evidence linking regular physical activity and brain health across the lifespan. Specifically, we will focus on the relationship between physical activity and brain health at three distinct stages of life: childhood and adolescence, mid-life, late life in cognitively healthy adults and later life in adults living with age-related neurodegenerative disorders such as Parkinson’s disease and Alzheimer’s disease.